DETERMINAN KEMISKINAN KOTA KENDARI TAHUN 2016 – 2022 - Utomo, Agus Prio; Rahman, Muljibir (Robust: Research of Business and Economics Studies, 2025)
This study aims to conduct a study on changes in poverty reviewed from several factors by including several aspects including school participation rates, unemployment rates, household expenditure per capita levels and the amount of regional spending used by local governments. Unlike previous studies that only saw poverty as personal behavior, this time it includes government spending as a variable that underlies the study of changes in the number of poor people in a certain time span with alternative policies as choices. The method used in this study is Multiple Regression Analysis testing. The findings in this study related to factors that drive changes in the number of poverty based on the calculation results show a coefficient of determination (R2) of 99.4%. With the most significant factor being Kendari city government spending with a coefficient value of 0.306.